Respuesta :

Answer:

8

Step-by-step explanation:

We can use the Polynomial Remainder Theorem. The PRT states that if we have a polynomial [tex]f(x)[/tex] being divided by a factor in the form of [tex](x-a)[/tex], then the remainder of the polynomial is given by [tex]f(a)[/tex].

We have the polynomial:

[tex]f(x)=3x^{15}-5x^{12}+7x^6-3x^2+12[/tex]

And it is being divided by:

[tex](x+1)[/tex]

We can rewrite our factor as:

[tex](x-(-1))[/tex]

Therefore:

[tex]a=-1[/tex]

Then our remainder will be:

[tex]f(-1)[/tex]

Evaluate:

[tex]\begin{aligned} f(-1)&=3(-1)^{15}-5(-1)^{12}+7(-1)^6-3(-1)^2+12\\&=-3-5+7-3+12\\&=8 \end{aligned}[/tex]

So, our remainder will be 8.  

ACCESS MORE